2022
DOI: 10.1038/s41598-022-10461-z
|View full text |Cite
|
Sign up to set email alerts
|

Carry-over effects of dry period heat stress on the mammary gland proteome and phosphoproteome in the subsequent lactation of dairy cows

Abstract: Exposure to heat stress during a cow’s dry period disrupts mammary gland remodeling, impairing mammary function and milk production during the subsequent lactation. Yet, proteomic changes in the mammary gland underlying these effects are not yet known. We investigated alterations in the mammary proteome and phosphoproteome during lactation as a result of dry period heat stress using an isobaric tag for relative and absolute quantitation (iTRAQ)-based approach. Cows were cooled (CL; n = 12) with fans and water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Dry cows are not only susceptible to thermal stress during lactation but also during the dry period that precedes lactation. Cows exposed to HS during the dry period have been found to exhibit altered postabsorptive metabolism and produce signi cantly less milk during the subsequent lactation, with reductions ranging from 3 to 7.5 kg/d [8,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Dry cows are not only susceptible to thermal stress during lactation but also during the dry period that precedes lactation. Cows exposed to HS during the dry period have been found to exhibit altered postabsorptive metabolism and produce signi cantly less milk during the subsequent lactation, with reductions ranging from 3 to 7.5 kg/d [8,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Because lactating dairy cows are more thermolabile than non-lactating cows. Skibiel et al [26] observed that the rectal temperature of lactating cows was 0.9°C higher than that of prepartum cows under similar environmental conditions. According to Thornton et al [30], a cow's rectal temperature is 38.5°C under normal conditions and 39.5°C under heat stress conditions.…”
Section: Heat Stress Indicators In Dairy Cattlementioning
confidence: 98%
“…Rectal temperature can be used as an indicator to identify the beginning of heat stress in animals produced by the microenvironment and nutrition [25]. Calves' and adult dairy cows' normal respiratory rates vary from 20-40 to 15-35 breaths/min, respectively [26]. As air temperature rises, changes in respiratory rate occur, causing the animals to breathe more frequently to dissipate heat [25].…”
Section: Heat Stress Indicators In Dairy Cattlementioning
confidence: 99%
See 2 more Smart Citations